Health-related quality of life on tele-monitoring for users with pacemakers 6 months after implant: the NORDLAND study, a randomized trial - Lopez-Villegas, Antonio; Catalán-Matamoros, Daniel; Lopez-Liria, Remedios; Enebakk, Terje; Thunhaug, Hilde; Lappegård, Knut Tore (BMC Geriatrics, 2018)
Source at https://doi.org/10.1186/s12877-018-0911-3. © The Author(s). 2018 Background : With an ageing population and widening indications for pacemakers implantation, the number of persons carrying an implant is steadily increasing. The routine follow-up is thus a heavy burden for the respective NHS as well as for the patients and their relatives. Most of them of the studies have been performed in densely populated areas and nearby to the hospital. It is thus unknown whether these results could be applied also in rural areas such as Northern Norway with a more scattered population. The aim of this study was to assess the effectiveness of telemonitoring (TM) in patients with pacemakers regarding reliability, safety and health-related quality of life, compared to traditional follow-up in outpatient clinic in a setting where geographical effects could possible influence the results. Methods : The NORDLAND study is a controlled, randomized, non-masked clinical trial in pacemaker patients, with data collection carried out during the pre-implant stage and after 6 months. Between August of 2014 and November of 2015, 50 patients were assigned to either a tele-monitoring group ( n = 25) or a conventional hospital monitoring (HM) group ( n = 25). The EuroQol-5D (EQ-5D) utilities and visual analogue scale (VAS) and the Minnesota Living with Heart Failure Questionnaire ( MLHFQ ) were used to measure Health-Related Quality of Life. Baseline characteristics and number of hospital visits were also analyzed. Results : The baseline characteristics of the two study groups were similar for EQ-5D utilities (TM:0.81; HM:0.76; p = 0.47), EQ-5D VAS (TM: 64.00; HM:64.88; p = 0.86) and the MLHFQ (TM:20.20; HM:28.96; p = 0.07). At the 6 month follow-up, there were no significant differences between the groups in EQ-5D utilities (TM: 0.81; HM: 0.76; p = 0.54) and EQ-5D VAS scores (TM: 72.71; HM: 59.79; p = 0.08 ). The MLHFQ score was improved in both groups (TM: -4.40; HM: -15.13; p < 0.001). The number of in-office visits was ...